2018
DOI: 10.4085/1302112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Management of Sport-Related Concussion Teaching Trends in Athletic Training Programs

Abstract: Context: Previous research suggests that health care providers, in general, are not adequately trained in sport-related concussion (SRC) recognition and management. However, it is unclear if athletic training educators are instructing athletic training students on evidence-based SRC assessment and management protocols. Objective: To examine and identify which SRC resources and management tools are being used to teach and prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…27,28 Evidence supporting strategies for both vestibular and oculomotor impairment and symptoms is limited but shows promise in assisting in the SRC evaluation process. 29,30 Finally, we observed no differences in self-efficacy for any other SRC assessment or management tools, such as the computerized neuropsychological testing, SCAT3, symptom checklist, or baseline examinations. This could be explained by the ready availability and regular use of these tools by a majority of ATs.…”
Section: Discussionmentioning
confidence: 64%
“…27,28 Evidence supporting strategies for both vestibular and oculomotor impairment and symptoms is limited but shows promise in assisting in the SRC evaluation process. 29,30 Finally, we observed no differences in self-efficacy for any other SRC assessment or management tools, such as the computerized neuropsychological testing, SCAT3, symptom checklist, or baseline examinations. This could be explained by the ready availability and regular use of these tools by a majority of ATs.…”
Section: Discussionmentioning
confidence: 64%
“…with 3DEditor. Later, the effect processing with Material Editor finally enters the keyflamer for the button screen editing of the key action point [12][13][14][15]. After completing these five parts, the system will automatically generate the transition of the intermediate connection motion, complete the movement, rotation, subversion, and change of the action, and develop two software for the special action.…”
Section: Software Environmentmentioning
confidence: 99%
“…These findings highlighted potential deficits in concussion education at the undergraduate level. Recently, Wallace et al 32 reported that more than 80% of athletic training education programs were teaching tools included in the 3-domain minimum concussion battery, but not all were providing hands-on experience with those tools. In addition, almost 30% were not teaching students about return-to-participation progressions.…”
Section: Concussion-assessment and -Management Differences Among Pracmentioning
confidence: 99%
“…In addition, almost 30% were not teaching students about return-to-participation progressions. 32 Educators should strive to remain up to date on concussion practices to ensure that the information is disseminated to future clinicians, and clinicians should aim to implement current recommendations in practice.…”
Section: Concussion-assessment and -Management Differences Among Pracmentioning
confidence: 99%